Pandangan Nurcholish Madjid Tentang Politik Hukum Islam (Kritik Fiqhisme dalam Konteks Orientalisme Modern) - Afrohatul Laili; Wildanul Ulum; Moh Komarudin; Erdi Auliya Azzahra (SINDA: Comprehensive Journal of Islamic Social Studies, 2025)
Nurcholis Majid views Islamic law through various criticisms, one of which is criticizing the study of fiqh (fiqhism) in the context of modern orientalism. This research uses the library research method with a descriptive qualitative approach. Madjid rejects fiqhism as a codification of outdated laws from the early Hijri era which was used by Western orientalism to view Islam in a rigid legalistic way, and proposes secularization as a process of making worldly things proportional to rational politics. The results of his thinking show that reforming Islamic law into a universal ethic that is compatible with Pancasila and Indonesian democracy, against post-colonial orientalistic distortions. Madjid emphasized the relevance of secularization for current contextual ijtihad.